2016
DOI: 10.1098/rsta.2015.0201
|View full text |Cite
|
Sign up to set email alerts
|

Wave–turbulence interaction-induced vertical mixing and its effects in ocean and climate models

Abstract: Heated from above, the oceans are stably stratified. Therefore, the performance of general ocean circulation models and climate studies through coupled atmosphere–ocean models depends critically on vertical mixing of energy and momentum in the water column. Many of the traditional general circulation models are based on total kinetic energy (TKE), in which the roles of waves are averaged out. Although theoretical calculations suggest that waves could greatly enhance coexisting turbulence, no field measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 46 publications
2
80
0
1
Order By: Relevance
“…Field data have revealed that this kind of interaction is phase‐locking, i.e., the wave‐turbulence interaction happens in the trough of surface wave [ Qiao et al . ]. In (5), α is constant and set to 1.0, Etrue(ktrue) represents the wave number spectrum and can be calculated from a numerical wave model, ω is wave angular frequency, k is wave number, and z is depth.…”
Section: The Physical Processes We Explorementioning
confidence: 99%
“…Field data have revealed that this kind of interaction is phase‐locking, i.e., the wave‐turbulence interaction happens in the trough of surface wave [ Qiao et al . ]. In (5), α is constant and set to 1.0, Etrue(ktrue) represents the wave number spectrum and can be calculated from a numerical wave model, ω is wave angular frequency, k is wave number, and z is depth.…”
Section: The Physical Processes We Explorementioning
confidence: 99%
“…This method is a general data‐driven method without any a priori basis functions, and the signal is decomposed based on the local characteristics of the data. It has been successfully applied to the eddy‐covariance analysis of air–sea interface turbulent fluxes (Wang et al ), ADV data processing (Qiao et al ), and geophysical studies (Huang and Wu )…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…Qiao et al () showed that the EMD can effectively remove the noise in the ADV data, in which the ADV vertical velocity was decomposed into 12 IMFs, and components 1 and 2 were treated as noise because they have characteristics of white noise. In our ADV datasets, the first few components of IMFs are also associated with Doppler noise and high‐frequency contamination.…”
Section: Materials and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors for the articles in this theme issue stem from many different fields, including applied mathematics (with articles on new theoretical developments by Cicone et al [1]; Daubechies et al [2]; Hou & Shi [3]; Joliffe & Cadima [4]; and Mallat [5]), physics (Meignen et al [6]), physiology (Yeh et al [7]), general science and data analysis (Huang et al [8]), meteorology and climate (Qiao et al [9] and Wu et al [10]) and biomedical research (Hemakom et al [11]). …”
mentioning
confidence: 99%